The world's heritage a complete guide to the most extraordinary places. - Unesco (London Collins Paris Unesco, 2009)
A guide to 878 UNESCO World Heritage sites, this publication is illustrated with over 650 full-color photographs. Location maps for every site are also included.--Publisher's description.
Keywords: World Heritage areas; Historic sites; Historic buildings; Civilization, Ancient